Efforts to Overcome Obstacles to Bailout Funds for KGPN Cooperative Customers in Medan Tembung District - Perkasa, Ripho Delzy; Ramadhan, Nugraha Pratama; Zaki, Ahmad (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research aims to determine the factors that cause problematic credit at the KGPN Cooperative, Medan Tembung District. This research uses qualitative research with interview observation and documentation methods. The problems in this research are: 1. What causes Bad Credit in Cooperatives? 2. What are the Efforts to Pay Off Loans for Cooperative Members Who Bail Out Customers of the Medan Tembung District KGPN Cooperative? The effort to resolve the loan bailout from cooperative members which was bailed out by KGPN Cooperative customers in Medan Tembung District is to carry out good communication with customers. If you don't get results, you will contact someone close to the customer. Cooperatives are the implementation of chapter 33 of the Constitution as regulated in Law Number 25 of 1992 concerning Cooperatives. Cooperatives in Indonesia have a big influence on the survival of local residents. Moreover, in cooperatives there are several cooperative members and non-cooperative members who are not punctual in returning their debts at the predetermined time. Bad credit in savings and loan cooperatives has become a matter of great concern for the health of the cooperative itself. Bad debts in cooperatives are increasing over time and are difficult to collect. Gutter funds are widely used in the current transaction process. Such as implementing the pay late concept which uses bailout funds first. So that the main payment is made in accordance with the terms and policies of both parties. In other cases, bailout funds can be applied to various transaction areas, not only buying and selling transactions.